Powers and terrains of ambiguity in the field of urban self-organization today - Ostanel, Elena; Attili, Giovanni (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2018)
In this brief Introduction we would discuss powers and terrains of ambiguity in the field of urban self-organization in cities today, particularly as concern the relation with local governments as well as their transformative potential in local communities.